PENGARUH KOMPENSASI EKSEKUTIF, KEPEMILIKAN SAHAM EKSEKUTIF, PREFERENSI RISIKO EKSEKUTIF DAN LEVERAGE TERHADAP PENGHINDARAN PAJAK (TAX AVOIDANCE) - Cindy Mayangsari; Zirman Zirman; Eka Haryani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This research aimed to test: 1) the influence of executive compensation to tax Avoidance, 2) the influence of the executive stock ownership to tax Avoidance, 3) the influence of the executive risk preferences against tax Avoidance and 4) the effect of leverage to tax Avoidance. The sample used in this study are all companies listed on the Indonesia Stock Exchange in 2010-2013 with purposive sampling technique. Data collection method was nonparticipant observation. Data analysis using Multiple Regression with the help of a computer program SPSS version 17.0. The results showed that: 1) executive compensation have significant effect on tax Avoidance, 2) executive stock ownership is significant effect on tax Avoidance, 3) there is no significant effect of executive risk preferences on tax evasion and 4) leverage have significant effect on tax Avoidance.Keywords : Compensation, Ownership, Risk, Leverage, and Tax Avoidance.